2012
DOI: 10.1021/nn303030t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vivo Pharmacokinetic Evaluation of Degradable Shell Cross-Linked Polymer Nanoparticles with Poly(carboxybetaine) versus Poly(ethylene glycol) Surface-Grafted Coatings

Abstract: Nanoparticles with tunable pharmacokinetics are desirable for various biomedical applications. Poly(ethylene glycol) (PEG) is well known to create “stealth” effects to stabilize and extend the blood circulation of nanoparticles. In this work, poly(carboxybetaine) (PCB), a new non-fouling polymer material, was incorporated as surface-grafted coatings, conjugated onto degradable shell crosslinked knedel-like nanoparticles (dSCKs) composed of poly(acrylic acid)- based shells and poly(lactic acid) (PLA) cores, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 59 publications
3
73
0
Order By: Relevance
“…pCBs have drawn special interests for their advantages over other zwitterionic materials, including versatile structural options, [8,9] simple synthetic approaches, [16] capability of further functionalization, [8,[17][18][19] ultra-low protein fouling and biofouling levels, [20,21] as well as good biocompatibility. [22][23][24][25] Zwitterionic pCB materials have many derivatives (Figure 1). Their properties and functions can be adjusted at the monomer level.…”
mentioning
confidence: 99%
“…pCBs have drawn special interests for their advantages over other zwitterionic materials, including versatile structural options, [8,9] simple synthetic approaches, [16] capability of further functionalization, [8,[17][18][19] ultra-low protein fouling and biofouling levels, [20,21] as well as good biocompatibility. [22][23][24][25] Zwitterionic pCB materials have many derivatives (Figure 1). Their properties and functions can be adjusted at the monomer level.…”
mentioning
confidence: 99%
“…Zwitterionic nanocarriers based on carboxybetaine acrylate also significantly resisted the nonspecific adsorption of serum proteins [68]. Biodistribution studies demonstrated that zwitterionic poly(carboxybetaine) surface-grafted nanoparticles had comparable in vivo pharmacokinetic profiles to their PEG-conjugated counterparts [69]. The excellent anti-fouling properties of zwitterionic nanocarriers make a promising alternative to conventional PEG coating for "stealthy" formulations [70].…”
Section: Zwitterionic Nanocarriersmentioning
confidence: 99%
“…Synthetic polymers play a major role in therapeutic drug, protein and gene delivery systems [1][2][3][4][5][6]. Among synthetic polymers (Scheme 1), poly (ethylene glycol) and its derivatives show potential applications in gene and drug delivery due to their solubility, nontoxicity and biocompatibility [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Among synthetic polymers (Scheme 1), poly (ethylene glycol) and its derivatives show potential applications in gene and drug delivery due to their solubility, nontoxicity and biocompatibility [1][2][3]. Dendrimers (Scheme 1) are also unique synthetic macromolecules of nanometer dimensions with a highly branched structure and globular shape with strong affinity towards DNA and RNA complexation [4][5][6][7][8][9][10]. It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%